N-Acyl migration in ceramides - Helena Van Overloop (Journal of Lipid Research, 2005)
Upon exposure of truncated ceramides, such as N-acetyl-sphingenine, and long-chain ceramides to moderate acidic conditions, three derivatives are formed. Two of them turned out to be O-acylated sphingenine, 1-O- and 3-O-acyl-sphingenine, and the other was identified as sphingenine. Truncated dihydroceramides (e.g., N-acetyl- and N-hexanoyl-sphinganine) also show this type of rearrangement, which is therefore not related to the presence of the allylic hydroxy group or to the length of the N-acyl chain. Of particular concern is the fact that the O-acylated compounds, which can be considered sphingoid base analogs, can be formed in chloroform or chloroform-methanol mixtures upon storage. For long-term storage, methanol or dichloromethane is the preferred solvent.A procedure to document the presence/formation of such O-acylated sphingoid bases in ceramide solutions in the picomole range, based on reversed-phase chromatography after derivatization of their amino group with 6-aminoquinolyl-N-hydroxysuccinimidyl carbamate, is presented.